2022
DOI: 10.3390/coatings12020180
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of 6xxx Series Aluminum Alloys

Abstract: Due to their superior mechanical properties, formability, corrosion resistance, and lightweight nature, 6xxx series aluminum (Al) alloys are considered as a promising structural material. Nevertheless, the successful application of these materials depends on their response to the external environment. Recently, designers considered the surface properties an equally important aspect of the component design. Due to this concern, these alloys are subjected to varieties of surface modification methodologies. Many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…These particles impede the movement of dislocations and enhance the resistance to plastic deformation, thereby resulting in an increase in material hardness [53]. Furthermore, the uniform distribution of Si3N4 particles achieved through the stir casting technique ensures that the reinforcing effect is evenly distributed throughout the composite material [54][55]. This uniform dispersion contributes to consistent improvements in hardness across the material, leading to enhanced mechanical performance.…”
Section: Hardnessmentioning
confidence: 99%
“…These particles impede the movement of dislocations and enhance the resistance to plastic deformation, thereby resulting in an increase in material hardness [53]. Furthermore, the uniform distribution of Si3N4 particles achieved through the stir casting technique ensures that the reinforcing effect is evenly distributed throughout the composite material [54][55]. This uniform dispersion contributes to consistent improvements in hardness across the material, leading to enhanced mechanical performance.…”
Section: Hardnessmentioning
confidence: 99%
“…For instance, they are employed in the fabrication of aviation fixtures, furniture, railway vehicles, ships, trams, and pipelines. The primary alloying elements of the 6000 series aluminum alloys are magnesium and silicon, classifying them as heattreatable alloys [4,5]. The typical precipitation sequence for the 6000 series aluminum alloys is as follows: supersaturated solid solution (SSSS) → atomic clusters → GP zones (β ′′ precursors) → β ′′ → β ′ → β [6].…”
Section: Introductionmentioning
confidence: 99%
“…The surface modification methods of an aluminum alloy mainly include anodic oxidation, melt coating, and plating, and surface plating has the advantages of low cost and easy processing compared with other modification methods [4]. Polytetrafluoroethylene (PTFE) has the advantages of high-temperature resistance and low friction coefficient and has a wide range of applications in solid lubrication [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the PTFE coating filled with graphite and MoS 2 was prepared on the surface of 4032 aluminum alloy by spraying technique, the common methods to reduce the wear of the frictional subsets of scroll compressors are embedded seals or surface treatment, and the main frictional conditions are dry friction [3,17]. Therefore, under dry friction, the tribological properties were compared with the traditional surface modification methods of aluminum alloy: surface anodizing and surface Ni coating, and the comparison showed that the C-MoS 2 -PTFE coating has a greater advantage in wear reduction and abrasion resistance than the traditional surface modification methods [4]. And the tribological wear behavior of the coating was investigated, the wear morphology and composition of the coating were analyzed to reveal the tribological mechanism of C-MoS 2 -PTFE coating.…”
Section: Introductionmentioning
confidence: 99%